The Effect of Preinduction Cervical Ripening With Synthetic Hygroscopic Dilators on Maternal Outcomes of Women With Previous Caesarean Pregnancy: A Single-Group Clinical Trial - Gowri Dorairajan; Saranya Ravi; Palanivel Chinnakili (Journal of Pregnancy)
Conclusions: We conclude that the hygroscopic dilator Dilapan effectively ripens the cervix before labour induction in women with a previous caesarean scar. They are safe, but more extensive studies are needed to evaluate scar-related complications during labour.